2014
DOI: 10.1186/1471-2148-14-38
|View full text |Cite
|
Sign up to set email alerts
|

Discord between morphological and phylogenetic species boundaries: incomplete lineage sorting and recombination results in fuzzy species boundaries in an asexual fungal pathogen

Abstract: BackgroundTraditional morphological and biological species concepts are difficult to apply to closely related, asexual taxa because of the lack of an active sexual phase and paucity of morphological characters. Phylogenetic species concepts such as genealogical concordance phylogenetic species recognition (GCPSR) have been extensively used; however, methods that incorporate gene tree uncertainty into species recognition may more accurately and objectively delineate species. Using a worldwide sample of Alternar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 84 publications
2
77
0
Order By: Relevance
“…24 In particular, the SCAR marker OPA1-3 proved to be highly efficient in generating discriminant sequences. 6,9,20 In the present study, the alignment of the OPA1-3 sequences, belonging to Alternaria reference strains of the species/morphotypes, more commonly reported on citrus, showed evidence of a high degree of variability. Different informative SNPs were found that encouraged the screening of the entire Alternaria collection available by an HRM approach, since this technique allows the detection of even single base variations among samples.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…24 In particular, the SCAR marker OPA1-3 proved to be highly efficient in generating discriminant sequences. 6,9,20 In the present study, the alignment of the OPA1-3 sequences, belonging to Alternaria reference strains of the species/morphotypes, more commonly reported on citrus, showed evidence of a high degree of variability. Different informative SNPs were found that encouraged the screening of the entire Alternaria collection available by an HRM approach, since this technique allows the detection of even single base variations among samples.…”
Section: Discussionsupporting
confidence: 57%
“…Concerning the first one, several genetic regions with higher sequence variation, compared to more classical barcoding regions such as ITS or endopolygalacturonase, were identified in Alternaria genus, and used to estimate phylogenies among small‐spored species . In particular, the SCAR marker OPA1–3 proved to be highly efficient in generating discriminant sequences . In the present study, the alignment of the OPA1–3 sequences, belonging to Alternaria reference strains of the species/morphotypes, more commonly reported on citrus, showed evidence of a high degree of variability.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Stewart et al . () found a few putative recombination events in two anonymous DNA regions (Flank 3 and OPA1.3) for citrus brown pathogen A. alternata populations. Alternaria alternata / A. tenuissima populations from Pistacia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Stewart et al . () revealed phylogenetically distinct lineages within the citrus brown pathogen A. alternata from a worldwide collection of isolates, and Huang et al . () presented a novel phylogenetic reconstruction for the same pathogen in China.…”
Section: Introductionmentioning
confidence: 98%